The Role of Public Policy in Optimizing Village Original Income - Soselisa, Hendry Ch.; Stevany Timisela, Ria; Nahumamury, Nur Aini (Public Policy, 2025)
Village Original Revenue Management (PADesa) is very important for village development and is regulated in Article 71 of Law No. 6 of 2014. This research uses a qualitative approach, analyzing the capacity of village apparatus in income planning, source identification, and overall management. The findings reveal that the Horale State government has not effectively allocated PADesa funds. To improve revenue management, all stakeholders should engage in deliberative discussions and conduct a comprehensive inventory of revenue sources to improve financial sustainability.